Atomic weights of the elements, 1975 (IUPAC publication, 1976)
Atomic Weights of the Elements 1975 outlines the different problems that arise from the imprecise definition of atomic weight or relative atomic mass. This book reviews the natural isotopic composition of the elements and tabulates the relative atomic masses for selected radioisotopes. This book is comprised of one chapter. This text begins with an overview of the problems arising from the actual or potential variability of the atomic weights of several elements. This book then discusses the significance of having informative labels on chemicals that are commercially available. The reader is a.